2021
DOI: 10.1093/ecco-jcc/jjab224
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from Intravenous to Subcutaneous Vedolizumab in Patients with Inflammatory Bowel Disease [TRAVELESS]

Abstract: Background and Aims Subcutaneous (SC) vedolizumab presents the opportunity for inflammatory bowel disease (IBD) patients to manage their treatment at home. There is currently no data on the process of transitioning patients established on intravenous (IV) to SC as part of routine clinical care. The aim of this programme is to evaluate the clinical and biochemical outcomes of switching a cohort of IBD patients established on IV vedolizumab to SC 12 weeks following the transition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 25 publications
4
42
2
1
Order By: Relevance
“…In our study, serum vedolizumab trough concentrations at steady state were approximately twice as high during SC as compared with IV treatment. These findings are in line with the VISIBLE studies 4,5 and the study Ventress et al 6 Our results suggest an inverse relationship between serum vedolizumab trough levels and faecal calprotectin levels with vedolizumab given IV. However, after 6 months with SC vedolizumab at standard dose, this correlation was not seen.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, serum vedolizumab trough concentrations at steady state were approximately twice as high during SC as compared with IV treatment. These findings are in line with the VISIBLE studies 4,5 and the study Ventress et al 6 Our results suggest an inverse relationship between serum vedolizumab trough levels and faecal calprotectin levels with vedolizumab given IV. However, after 6 months with SC vedolizumab at standard dose, this correlation was not seen.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, the authors described a 52% increase (p < 0.01) in the patients' faecal calprotectin levels at the end of their study which was rather unexpected. 6 Thus, further studies are warranted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although limited by a lack of endoscopic assessment, and no comparator IV group, the study indicates maintained therapeutic efficacy, high treatment persistence and patient acceptability rates for the SC formulation. The findings extend the previous observations by Ventress et al which reported reassuring outcomes albeit with a shorter follow‐up duration of 12 weeks 8 . Intriguingly, serum vedolizumab levels increased after switching to SC and this may simply reflect steady‐state drug distribution with the SC formulation as opposed to better bioavailability.…”
supporting
confidence: 87%
“…8 Intriguingly, serum vedolizumab levels increased after switching to SC and this may simply reflect steady-state drug distribution with the SC formulation as opposed to better bioavailability. Similar findings have been reported in previous cohort studies of switching from IV to SC vedolizumab 8 as well as IV to SC infliximab. 9 Interestingly, previous reports suggest near-complete occupancy of α4β7 integrin in peripheral blood memory T cells regardless of drug levels 10 and this explains why the increased serum levels with SC vedolizumab may not necessarily translate to better clinical outcomes.…”
mentioning
confidence: 99%